DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP LANSIA DI PSTW BUDI SEJAHTERA BANJARBARU - Herawati; Wafroh, Siti; Lestari, Dhian Ririn (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Family support is the assistance given by other family members that will provide comfort. Familysupport is needed by the elderly to improve their quality of life. To determine the relationship offamily support with the quality of life of the elderly in PSTW Budi Sejahtera Banjarbaru.Observational study using cross sectional design. Respondents totaled 50 elderly with researchinstruments such as questionnaires family support and quality of life questionnaire WHOQOLOLD. Research showed that elderly people who had high levels of support for poor familiestotaling 23 people (46%), family support sufficient amounts to 12 people (24%), family supportboth numbering 12 people (24%) and family support is very good amount to 3 people (6% ).Elderly people who had a low level of quality of life totaled 3 (6%), quality of life was 36 (72%)and a high quality of life for a total of 11 people (22%). Analysis of data from this study usedSpearman Rank test obtained p value of 0.001 (p ˂ 0.05) which shall mean there was asignificant relationship between family support with the quality of life of the elderly in PSTWBudi Sejahtera Banjarbaru with r = 0.884, which means the power of strong relationships andhas a positive direction. The support given to the elderly a good family will improved the qualityof life of the elderly.